Geranyl Dihydrochalcones from Artocarpus altilis and Their Antiausteric Activity - Nguyen, Mai Thanh Thi; Nguyen, Nhan Trung; Nguyen, Khang Duy Huu; Dau, Hien Thu Thi; Nguyen, Hai Xuan; Dang, Phu Hoang; Le, Tam Minh; Nguyen Phan, Trong Huu; Tran, Anh Hai; Nguyen, Bac Duy; Ueda, Jun-ya; Awale, Suresh (Planta Medica, 2014)
Human pancreatic cancer cell lines have remarkable tolerance to nutrition starvation, which enables them to survive under a tumor microenvironment. The search for agents that preferentially inhibit the survival of cancer cells under low nutrient conditions is a novel antiausterity strategy in anticancer drug discovery. In this study, the methanolic extract of the leaves of Artocarpus altilis showed 100 % preferential cytotoxicity against PANC-1 human pancreatic cancer cells under nutrient-deprived conditions at a concentration of 50 µg/mL. Further investigation of this extract led to the isolation of eight new geranylated dihydrochalcones named sakenins A–H (1–8) together with four known compounds (9–12). Among them, sakenins F (6) and H (8) were identified as potent preferentially cytotoxic candidates with PC50 values of 8.0 µM and 11.1 µM, respectively.
Keywords: antiausterity agent; Artocarpus altilis; Moraceae; pancreatic cancer; PANC-1